PENGARUH OPINI AUDIT GOING CONCERN TERHADAP MODEL PREDIKSI KEBANGKRUTAN DAN REPUTASI AUDITOR - Muhammad Fadhill Lizaldy; Yulinda Yulinda (Pusat P2M Politeknik Negeri Batam, 2017)
Audit report with modification of going concern indicates that in auditor’s opinion there is a risk that companies could not survive. This study is aimed to investigate the effect of bankruptcy prediction model and auditor reputation on going concern audit opinion. Moreover, this going concern modification is not expected by companies due to decrease public trust of image company. In addition, some of companies received unqualified opinion stop operating and not in accordance with the auditor's assessment. Thus, this study used object includes manufacturer listed on Indonesia Stock Exchange during 2013 -2015 with 134 observations obtained using purposive sampling method. Furthermore, this data are analyzed used logistic regression analysis. The conclusion of this study, the result has showed that the financial condition proxied by bankruptcy prediction model affect going concern auditor opinion positively. The auditors reputation which is proxied by audit firm size do not positively affect the opinion.Keywords: going concern opinion, bankruptcy prediction model, auditor reputation